2023
DOI: 10.3390/molecules28145554
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous CuO Prepared in a Natural Deep Eutectic Solvent Medium for Effective Photodegradation of Rhodamine B

Abstract: Metal oxide nanoparticles (NPs) have been widely used as catalysts in the chemical industry, but their preparation is usually limited by strict conditions such as high temperature, elevated pressure, and the use of volatile and highly toxic organic solvents. To solve this problem, this work developed an environmentally benign method using green solvents, i.e., natural deep eutectic solvents (NADESs), as a reaction medium to prepare copper oxide (CuO) particles. The experimental results suggested that the synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…As the concentration of RhB increased, the limited active sites of UNM are occupied by more RhB molecules, resulting in a gradual decrease in degradation efficiency. 40 It is important to determine a reasonable concentration range, 41 and after reviewing the literature, it was concluded that 10−20 mg/L would be suitable. 42,43 The maximum degradation speed and rate within this concentration range were observed when the original concentration of RhB is 10 mg/L, as shown in the kinetic fitting diagram (Table S3).…”
Section: Characterization Of the Structure And Morphologymentioning
confidence: 99%
“…As the concentration of RhB increased, the limited active sites of UNM are occupied by more RhB molecules, resulting in a gradual decrease in degradation efficiency. 40 It is important to determine a reasonable concentration range, 41 and after reviewing the literature, it was concluded that 10−20 mg/L would be suitable. 42,43 The maximum degradation speed and rate within this concentration range were observed when the original concentration of RhB is 10 mg/L, as shown in the kinetic fitting diagram (Table S3).…”
Section: Characterization Of the Structure And Morphologymentioning
confidence: 99%
“…Additionally, this agglomeration can lead to secondary pollution in the water system, thereby limiting its effectiveness in degrading organic pollutants [10][11][12]. Therefore, it becomes imperative to develop an appropriate support substrate that can address these issues by facilitating the deposition of the catalyst [13].…”
Section: Introductionmentioning
confidence: 99%